FAKTOR-FAKTOR YANG MEMPENGARUHI PREDIKSI PERINGKAT OBLIGASI PADA PERUSAHAAN MANUFAKTUR DI BEI - ARVIAN PANDUTAMA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
This research aims at providing empirical evidence on factor that affect obligation ratings prediction. The variables on this research consist of leverage, size, profitability, growth, maturity, secure, and auditor reputation. The sample of this research consist of 11 manufacturing firms are listed in Indonesian Stock Exchange and rated by PT. PEFINDO from 2007-2010. The type of data used in this research was secondary data. Logistic regression is used to test the hypothesis. The result of this research shows that all variables generally can be the instrument for predicting the corporate bond rating. However, only secure is significant variable determining obligation ratings. Leverage, size, profitability, growth, maturity, and auditor reputation are insignificant variables determining obligation ratings. The result of this research indicates that in general, the obligation manufacturing firms in Indonesia are investment grade.